Catalytic cracking aid for improving gasoline octane number and preparation method thereof
By alkali treatment and acid modification of the MFI structure molecular sieve, combined with colloid formation of pseudo-thin aluminite, the problems of complex additive processes and increased liquefied gas yields are solved, and efficient and simple preparation of catalytic cracking additives are achieved, which significantly increases the gasoline octane number.
Patent Information
- Application Number
- CN202110181454.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-08
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-02-08
AI Technical Summary
While the existing catalytic cracking additives increase the octane number of gasoline, the yield of liquefied gas has also been greatly improved. The preparation process is complex, and there are problems such as hard agglomeration and hard binder curing, making it difficult to meet the efficient and simple production needs.
In the presence of organic base and/or inorganic base, the MFI structure molecular sieve is pre-base-treated to form secondary mesoporous and increase the outer specific surface area and mesoporous volume. Then mix with the slurry and acid to form an acid colloid, realize the acid modification and dispersion of the molecular sieve, and simplify the preparation process.
The prepared catalytic cracking additive has good wear resistance and a smooth pore structure, which can significantly increase the gasoline octane number without significantly increasing the yield of liquefied gas, and is simple in process and cost-saving.
Smart Images

Figure BDA0002941240080000131 
Figure BDA0002941240080000132 
Figure BDA0002941240080000141
Abstract
Description
Technical Field
[0001] The invention relates to a catalytic cracking aid, in particular to a catalytic cracking aid capable of improving the octane number of gasoline, with a small increase in the liquefied gas and improved propylene yield, and a preparation method thereof. Background Art
[0002] With the continuous growth of the consumption of high-grade gasoline (gasoline with a research octane number of 93 or above) in my country, the proportion of high-grade gasoline output has increased from 28.5% in 2003 to 56.5% in 2006. It is expected that the demand for high-grade gasoline will increase from 75% in 2010 to 94% in 2020. In addition to achieving high-grade gasoline, another major task of gasoline production is to make it clean. Since January 1, 2010, low-olefin environmentally friendly gasoline has been fully launched nationwide. In the process of gasoline cleaning, some measures, such as controlling the olefin content in gasoline and gasoline hydrodesulfurization, will lead to octane loss, and the contradiction of octane shortage will become more prominent.
[0003] Due to the high proportion of catalytic cracking gasoline in gasoline blending components in my country, which is generally around 75%, the proportion of high-grade gasoline output is still low. Therefore, further improving the octane number of FCC gasoline is the only way to upgrade gasoline products. There are many ways to improve the octane number of FCC gasoline, such as using octane-enhancing additives or high-octane cracking catalysts, optimizing the composition of catalytic cracking feedstock, changing the operating conditions of FCC units, etc. Among them, the use of octane-enhancing additives containing MFI-structured molecular sieves is one of the effective ways to quickly improve the octane number of FCC gasoline. The main active component for improving the octane number of gasoline is the molecular sieve with MFI structure, which has higher efficiency in additives than in the main agent, and because an additive can be used in combination with different main agents to meet the needs of different users for product distribution, it has higher flexibility. Therefore, for most catalytic cracking units, the use of additives with MFI-structured zeolites is an effective technical approach to improve the octane number.
[0004] CN 1465527A discloses a MFI structure zeolite containing phosphorus and transition metals. The anhydrous chemical expression of the zeolite is (0-0.3)Na2O·(0.5-5)Al2O3·(1.3-10)P2O5·(0.7-15)M2O3·(70-97)SiO2, calculated by the mass of the oxides, wherein M is selected from one of the transition metals Fe, Co and Ni. When the zeolite is used in the catalytic cracking process of petroleum hydrocarbons, the yield and selectivity of C2-C4 olefins can be improved, and the yield of liquefied gas is higher.
[0005] CN 1796496A discloses a cracking aid for increasing the concentration of propylene, which is composed of 10-65 wt% of modified ZSM-5 molecular sieve, 0-60 wt% of clay, 15-60 wt% of inorganic oxide binder, 0.5-15 wt% of one or more metal additives selected from Group VIIIB metals and 2-25 wt% of phosphorus additive on a dry basis, wherein the modified ZSM-5 molecular sieve is modified by phosphorus and a metal selected from Fe, Co or Ni, and the mass of the oxide is (0-0.3)Na2O·(0.5-5)Al2O3·(1.3-10)P2O5·(0.7-15)M x O y ·(70~97)SiO2. This additive is used in the catalytic cracking process to increase the yield of liquefied gas and the octane number of gasoline, while significantly increasing the propylene concentration in the liquefied gas.
[0006] CN 102049284 B discloses a catalytic cracking propylene additive and a preparation method thereof. The additive contains 30 to 80 weight percent of molecular sieves based on a total weight of 100 percent, wherein the content of ZSM-5 zeolite is 28 to 78 weight percent, and 10 to 65 weight percent of clay. The additive contains P, which is 5.0 to 20.0 weight percent, preferably 7.0 to 15.0 weight percent, in terms of P2O5, and the content of La2O3 is 0 to 1.0 weight percent. Aluminum phosphate sol is used as a binder to improve the wear resistance of the additive, increase the solid content of the spray slurry, and avoid the chlorine content on the spray slurry and the additive. The prepared catalytic cracking propylene additive has good dry gas and coke selectivity, and simultaneously improves the propylene yield and the gasoline octane number.
[0007] CN 106179470A discloses a method for preparing a catalytic cracking additive for improving the octane number of gasoline, and the preparation steps are as follows: (1) slurrying ZSM-5 molecular sieve with water, controlling the solid content to 35-45wt%, adding a certain proportion of modifier, and stirring evenly. (2) adding a certain proportion of pseudo-boehmite to the slurry of step (1), and adjusting its pH value to 1.8-2.3 with acid solution. (3) adding a certain concentration of pseudo-boehmite slurry to a certain concentration of phosphoric acid solution, controlling the reaction temperature to 50-65°C, and the reaction time to >5h. (4) adding a certain amount of water to the slurry of step (3), and then adding kaolin, and stirring evenly. (5) adding the slurry in step (2) to the slurry in step (4), and stirring evenly. (6) spray drying to obtain the additive. Industrial tests have shown that the additive accounts for 3-10wt% of the system reserves, and the research octane number can be increased by 1-3 units, and the propylene yield can be increased by 1-4 percentage points. The silicon-aluminum ratio of the ZSM-5 molecular sieve in the additive is 100-300.
[0008] CN 107971029 A discloses a catalytic cracking aid for increasing propylene production and a preparation method thereof. The catalytic cracking aid for increasing propylene production comprises, based on the dry weight of the aid, 10-75 weight % of a phosphorus-containing MFI structure molecular sieve in dry weight, 3-40 weight % of a phosphorus-aluminum inorganic binder in dry weight, 1-30 weight % of other inorganic binders in oxides, 0-60 weight % of a second clay in dry weight, and 0.5-15 weight % of a metal additive selected from at least one of Group VIII metals and manganese, zinc and gallium in oxides. The preparation method comprises: mixing the phosphorus-containing MFI structure molecular sieve, the phosphorus-aluminum inorganic binder and the other inorganic binders, adding or not adding the second clay, beating the pulp, and spray drying; wherein the metal additive is introduced, and the phosphorus additive is introduced or not. At the same time, the proportion of the mesopore volume of the phosphorus-containing MFI structure molecular sieve to the total pore volume is 40-70% by volume, and the proportion of the mesopore volume with a pore size of 2 nanometers to 20 nanometers to the total mesopore volume is more than 85% by volume; the proportion of the strong acid content of the molecular sieve to the total acid content is 45-75%, and the ratio of the B acid content to the L acid content is 8-30. The preparation method uses the phosphorus-containing MFI structure molecular sieve as a raw material, but the phosphorus-containing MFI structure molecular sieve needs to be processed by processes such as dealumination, phosphorus modification and roasting, and these processes directly affect the pore volume, pore size and other properties of the phosphorus-containing MFI structure molecular sieve, and the processing process of the molecular sieve of the invention is relatively cumbersome. In addition, the method also uses a phosphorus-aluminum inorganic binder as a raw material, and the binder solidification phenomenon is prone to occur during the preparation process of the phosphorus-aluminum inorganic binder, which means that the addition speed of phosphoric acid must be strictly controlled during production, and the production conditions and environment are demanding. At the same time, due to the high pH value during the preparation process, it is not conducive to the dealumination process of the molecular sieve.
[0009] Although the existing preparation technology of additives has solved some deficiencies and met the needs of additives in some aspects, the existing zeolite molecular sieves have been treated with metal and / or non-metal modification, roasting, etc., and the molecular sieve modification process is complicated. The modified molecular sieve has the problem of hard agglomeration, and it is also necessary to grind and other treatments to reduce its particle size before it can be used for the preparation of additives, otherwise it is not conducive to the anti-wear performance of the additives; the existing technology either prepares aluminum phosphate sol separately, and the concentration of phosphorus and aluminum is high during the preparation process, which may cause colloid instability and gelation, which is not conducive to the smooth production of additives; the use of pre-prepared aluminum phosphate to prepare catalytic cracking additives often has the problems of small pore volume and large stacking ratio, which is not conducive to fluidization, mass transfer and charring. The existing technology either improves the octane number of gasoline, but the yield of liquefied gas is also greatly increased. For refineries with limited recovery and utilization of liquefied gas, it is required that the additives increase the octane number of gasoline while the yield of liquefied gas is not increased much. The additives prepared by the existing technology also need to be further improved in terms of the performance of improving the octane number. Therefore, in order to reduce the difficulty of additive production, meet the requirements of improving gasoline octane number and other performance and ensure smooth production, despite the recent catalytic cracking additive technology for improving gasoline octane number, there is still a need for new technology for preparing additives for improving gasoline octane number with simple and feasible preparation process and further improved performance. Summary of the invention
[0010] The purpose of the present invention is to avoid the shortcomings of the above-mentioned technology and provide a catalytic cracking aid for improving the octane number of gasoline and a preparation method thereof, which is different from the existing method. The method of the present invention pre-treats the MFI structure molecular sieve with alkali in the presence of an organic base and / or an inorganic base. This process is beneficial to removing silicon in the molecular sieve, forming secondary mesopores, and increasing the external specific surface area and mesopore volume; at the same time, the molecular sieve is added before the pseudo-boehmite is acidified, and then mixed with the pseudo-boehmite and acid for slurrying, and contacted at a relatively low pH value of 0.1 to 2.0, so as to achieve the purpose of dispersing the pseudo-boehmite and acid-modifying the molecular sieve, so that the prepared catalytic cracking aid has good anti-wear performance and unobstructed pore structure, thereby promoting mass transfer and diffusion of reactants, intermediate transition states and product molecules in their pores, effectively improving the accessibility of the active center of the molecular sieve, so that the molecular sieve has good catalytic performance and reduces the occurrence of over-cracking and side reactions. The catalytic cracking aid of the present invention does not require the separate preparation of aluminum phosphate colloid, nor does it require the molecular sieve to be impregnated, filtered, roasted, etc. The preparation process is simple, the solid content of the colloid slurry is high, the prepared catalytic cracking aid has a large pore volume and good anti-wear performance, and can significantly improve the octane number of gasoline without significantly increasing the yield of liquefied gas.
[0011] The catalytic cracking aid for improving the octane number of gasoline disclosed in the present invention contains, based on the mass of the aid as 100%, 10-55% of MFI structure molecular sieve with a silicon oxide / aluminum oxide molar ratio of 100-450 on a dry basis, 10-55% of clay on a dry basis, 3-20% of pseudo-boehmite on a dry basis, 5-20% of phosphorus on an oxide basis, 0-10% of a binder on an oxide basis, and 0.2-6% of a modified metal compound on an oxide basis. The catalytic cracking aid is obtained by the following preparation method: the MFI structure molecular sieve is treated with alkali in advance; before the pseudo-boehmite is acidified, the alkali-treated MFI structure molecular sieve is added and acidified to form an acidified colloid with a pH value of 0.1-2.0; the acidified colloid is homogenized and directly spray-dried, roasted, and washed with water to obtain the catalytic cracking aid for improving the octane number of gasoline.
[0012] The catalytic cracking additive for improving the octane number of gasoline disclosed in the present invention contains, based on 100% of the additive mass, 20-45% of MFI structure molecular sieves calculated on a dry basis, 15-40% of clay calculated on a dry basis, 5-15% of pseudo-boehmite calculated on a dry basis, 10-18% of phosphorus calculated on an oxide basis, 0-5% of a binder calculated on an oxide basis and 0.3-4% of a modified metal compound calculated on an oxide basis.
[0013] The catalytic cracking aid for improving the octane number of gasoline disclosed in the present invention, wherein the clay is at least one selected from kaolin, metakaolin, sepiolite, rectorite, montmorillonite and diatomite; the binder is at least one selected from alumina sol and aluminum chloride; the phosphorus is at least one selected from phosphoric acid, diammonium hydrogen phosphate, diammonium dihydrogen phosphate and ammonium phosphate; the modified metal compound is at least one selected from transition metal compounds and metal compounds of Group IIIB in the periodic table. The transition metal compound is at least one selected from compounds containing Fe, Ni, Cu, Mn or Zn, including halides, nitrates, sulfates of water-soluble transition metal elements, oxides, hydroxides, carbonates of water-insoluble transition metal elements, as one or more thereof. The IIIB group metal in the periodic table is selected from one or more of Y and lanthanide rare earths, and the lanthanide rare earth is selected from at least one of lanthanum-rich rare earths, cerium-rich rare earths, pure lanthanum or pure cerium, including water-soluble halides, nitrates, sulfates, compounds rich in IIIB group elements, and water-insoluble oxides, hydroxides, and carbonates of IIIB group elements, as one or more thereof.
[0014] The catalytic cracking aid for improving the octane number of gasoline disclosed in the present invention, wherein the alkali treatment is: MFI structure molecular sieve is mixed with water and alkaline substance, and stirred at 10-80°C for 0.5h-2h. The molecular sieve: alkaline substance: water (molecular sieve dry basis, weight ratio) is 100: (2-50): (100-1500).
[0015] The catalytic cracking aid for improving the octane number of gasoline disclosed in the present invention, wherein the alkali treatment is: MFI structure molecular sieve is mixed with water and alkaline substance, and stirred at 15-40°C for 0.5h-1h. The molecular sieve: alkaline substance: water (molecular sieve dry basis, weight ratio) is 100: (4-20): (120-1000).
[0016] The catalytic cracking aid for improving the octane number of gasoline disclosed in the present invention, wherein in the alkali treatment process, the alkaline substance is selected from one or more of organic alkali and inorganic alkali compounds; the inorganic alkali is selected from one or more of ammonia water, urea, sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium carbonate, potassium bicarbonate, potassium hydroxide, water glass, and sodium silicate; the organic alkali is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrapropylammonium hydroxide.
[0017] The catalytic cracking aid for improving the octane number of gasoline disclosed in the present invention, wherein the preparation method of the aid can be: the MFI structure molecular sieve treated with alkali, water and acid are uniformly mixed to make the pH value of the slurry within the range of 2.0 to 6.5, then the modified metal compound and clay are added for slurrying for 15min to 60min to form a mixed slurry A, pseudo-boehmite is added to form a slurry B, the pH value of the slurry B is adjusted to within the range of 0.1 to 2.0 with acid, and then aged at 40 to 60°C for 30min to 60min, cooled to below 35°C, a binder and a phosphorus compound are added, homogenized, spray-dried, roasted and washed with water to obtain the catalytic cracking aid for improving the octane number of gasoline.
[0018] In the above process, the MFI structure molecular sieve can be sodium type or can be treated by ion exchange and sodium reduction. The molecular sieve is treated with alkali in contact with alkaline substances, which is conducive to removing silicon from the molecular sieve, forming secondary mesopores, and increasing the external specific surface area and mesopore volume of the molecular sieve; mixing with acid for pulping is conducive to further removing amorphous silicon and aluminum that block the pores in the molecular sieve, reducing the particle size of the molecular sieve and making the pores smoother. At the same time, the modified metal compound and the molecular sieve undergo ion exchange to modify the molecular sieve. Pseudoboehmite and acid are added to slurry A to form slurry B, so that the pseudoboehmite is peptized and dispersed. At the same time, the MFI structure molecular sieve continues to contact with acid to ensure the full removal of its amorphous silicon and aluminum and the full dispersion of the molecular sieve particles. After adding phosphorus compounds and binders, the phosphide reacts with the molecular sieve, pseudoboehmite, and binder to achieve the purpose of phosphorus-modified molecular sieve, phosphorus-modified pseudoboehmite, and phosphorus-modified binder, so that the gelling system finally forms a stable and uniform colloid.
[0019] The catalytic cracking aid for improving the octane number of gasoline disclosed in the present invention can also form the slurry A in the preparation process as follows: the MFI structure molecular sieve is pre-treated with alkali, then mixed evenly with water and acid to make the pH value of the slurry within the range of 2.0 to 6.5, and a modified metal compound is added to perform slurrying for 15 to 45 minutes to allow the modified metal ions to first modify the molecular sieve, and then phosphoric acid and / or at least one of diammonium hydrogen phosphate, diammonium phosphate, and ammonium phosphate are added, and other acids, such as one or more of hydrochloric acid, nitric acid, and sulfuric acid, can also be added at the same time to perform phosphorus modification and acid modification on the molecular sieve, and the slurrying is continued for 15 minutes to form slurry A.
[0020] The catalytic cracking aid for improving the octane number of gasoline disclosed in the present invention can also be prepared by: the MFI structure molecular sieve is treated with alkali in advance, and then mixed with water and acid to make the slurry pH value in the range of 2.0 to 6.5, and then the modified metal compound, pseudo-boehmite, clay, and acid are added for mixing and beating to form slurry C, and the pH value of the slurry C is in the range of 0.1 to 2.0, and then aged at 40 to 60°C for 30 minutes to 60 minutes, cooled to below 35°C, and a binder and a phosphorus compound are added, spray dried, roasted, and washed with water to obtain the catalytic cracking aid for improving the octane number of gasoline. This preparation process is simple, and the alkali-treated MFI structure molecular sieve, water, pseudo-boehmite, clay, and acid form slurry C. Under the acidic condition of pH value 0.1 to 2.0, the metal compound modified molecular sieve and the dispersion of molecular sieve and pseudo-boehmite are achieved, and the molecular sieve acid extracts amorphous silicon aluminum and dredges the pores.
[0021] During the preparation of the additive of the present invention, it is determined whether to perform water washing and sodium reduction treatment on the additive according to the sodium oxide content in the additive, so that the sodium oxide content of the final additive is less than 0.3%. The water washing adopts the commonly used ammonium salt exchange, acid exchange and other methods in the prior art.
[0022] In the process of the present invention, the alkali-treated MFI structure molecular sieve does not need to be filtered, etc., and can be directly used for the preparation of the auxiliary agent. In addition, phosphorus is directly added to the gelling system, and compared with the formation of aluminum phosphate colloid or phosphorus-containing MFI structure molecular sieve alone, the phosphorus-containing colloid is more stable and not easy to gel because the concentration of phosphorus in the system is relatively low. In the process of the present invention, the molecular sieve slurry is directly used to disperse kaolin, pseudo-boehmite, etc., and the solid content of the gelling slurry is high, which can reach 35%-45%. Compared with the existing technology of forming aluminum phosphate colloid, phosphorus-containing MFI structure molecular sieve alone, and filtering, washing, etc. of the molecular sieve after alkali treatment, the preparation process of the auxiliary agent of the present invention is simplified, and the prepared auxiliary agent has better anti-wear performance and larger pore volume.
[0023] The catalytic cracking additive for improving the octane number of gasoline disclosed in the present invention, wherein the acid used is at least one selected from hydrochloric acid, nitric acid, phosphoric acid, oxalic acid, citric acid, and formic acid; and the amount of acid added is such that the pH value of the mixed slurry is within the required range. If phosphoric acid is used to adjust the pH value of the mixed slurry A, slurry B, slurry C, etc., it is best to select at least one selected from hydrochloric acid, nitric acid, oxalic acid, citric acid, and formic acid to ensure that the pseudo-boehmite is fully dispersed, thereby ensuring that the additive of the present invention has good anti-wear performance.
[0024] The catalytic cracking aid for improving the octane number of gasoline disclosed in the present invention, wherein the binder can be added in any step of the gelling process, and is not limited by the order of addition. For example, it can be added before the pseudo-boehmite is acidified, or it can be added after the pseudo-boehmite is acidified.
[0025] The main advantages and effects of the present invention are:
[0026] The catalytic cracking aid disclosed in the present invention has the advantages that firstly, the raw material MFI structure molecular sieve of the present invention is simple and does not need to go through complicated processing steps such as dealumination, phosphorus modification and roasting. Only the untreated raw material MFI structure molecular sieve needs to be selected, thereby saving the preparation cost of the molecular sieve and the aid.
[0027] Secondly, the MFI structure molecular sieve is treated with alkali, and then an organic acid and / or an inorganic acid, a modified metal compound is used to modify the MFI structure molecular sieve with a silicon oxide / aluminum oxide molar ratio of 100 to 450 and perform an acid extraction treatment under the premise of the presence or absence of pseudo-boehmite. The molecular sieve is treated with alkali and acid respectively, which is conducive to removing silicon and aluminum in the molecular sieve, forming mesopores, improving the pore structure of the molecular sieve, improving the accessibility of the reactant product molecules to the active center of the molecular sieve, and is conducive to dispersing the molecular sieve and pseudo-boehmite. At the same time, the modified metal compound and the molecular sieve undergo ion exchange, thereby modifying the molecular sieve to obtain a catalytic cracking aid with improved reaction performance and anti-wear performance; the metal compound modification can improve the propylene yield and propylene selectivity. The additive of the invention does not require the molecular sieve to be impregnated, filtered, roasted, ground and crushed, etc., has a simple preparation process, a high solid content of the colloid, stable colloid properties, a large pore volume and good anti-wear performance, and can significantly improve the octane number of catalytic cracking gasoline, and improve the propylene yield and propylene selectivity.
[0028] Furthermore, the present invention does not require the pre-preparation of the phosphorus-aluminum inorganic binder, thereby simplifying the preparation process of the auxiliary agent. In the technology of pre-preparing the phosphorus-aluminum inorganic binder, the addition speed of phosphoric acid must be strictly controlled during production, which brings inconvenience in production and the problem of stable production. In the preparation process of the auxiliary agent of the present invention, the addition time of phosphoric acid is not very strictly limited, and the problem of adhesive curing is not easy to occur.
[0029] The catalytic cracking aid of the invention has good catalytic cracking performance and can effectively improve the gasoline octane number and propylene yield after being mixed with the main agent and used in hydrocarbon oil catalytic cracking reaction. DETAILED DESCRIPTION
[0030] The present invention is further described below with reference to examples, but the present invention is not limited to these examples.
[0031] (A) Analytical testing methods used in the examples.
[0032] 1. Sodium oxide, phosphorus, silicon oxide and aluminum oxide content: analyzed by X-ray fluorescence method.
[0033] 2. Specific surface area and pore volume: The test was conducted using the Autosorb-6B physical adsorption instrument produced by Quantachrome, USA. Before the test, the sample was pre-treated by vacuum degassing at 300°C for 8 hours to remove moisture and impurities in the sample, and then adsorption-desorption analysis was performed under liquid nitrogen temperature of 77K. The specific surface area and pore volume were calculated using the BET and BJH equations, respectively.
[0034] 3. The particle size of the molecular sieve was analyzed by laser particle size analyzer. The anti-wear performance of the catalytic cracking additive was analyzed by MS-C / 6 wear index analyzer produced by Shenyang Kehui Instrument Manufacturing Co., Ltd.
[0035] 4. Catalyst cracking reaction performance evaluation: It was carried out on the ACE-MODEL R+MM evaluation device. The catalyst was pre-treated at 800°C and 100% steam for 17 hours. The reaction raw material was 3 million tons / year of heavy catalyst crude oil from Lanzhou Petrochemical Company. The reaction conditions were a catalyst-to-oil ratio of 5.0 and a reaction temperature of 530°C.
[0036] (ii) Specifications of raw materials used in the examples.
[0037] 1. Kaolin (ignition loss 18.6%), diatomite (ignition loss 15.4%), pseudo-boehmite (ignition loss 36.4%), aluminum sol (containing 21.2% by weight of aluminum oxide), ZSM-5 molecular sieve A (silicon-aluminum molar ratio 102, Na2O content 0.10%, crystallinity 90%, median particle size 7.8μm, specific surface area 340m 2 / g, mesopore volume 0.08mL / g), ZSM-5 molecular sieve B (silicon-aluminum molar ratio 250, Na2O content 0.08%, crystallinity 85%), NaZSM-5 molecular sieve (silicon-aluminum molar ratio 250, Na2O content 2.95%): all are industrial products, collected from the catalyst plant of Lanzhou Petrochemical Company.
[0038] 2. Ferrophosphorus modified ZSM-5 molecular sieve (silicon to aluminum molar ratio 36, Na2O content 0.10%, P2O5 content 4.51%, Fe2O3 content 2.1%): prepared by the method disclosed in CN1465527A.
[0039] 3. Aluminum chloride, formic acid, oxalic acid, citric acid, nitric acid (>65% by weight), hydrochloric acid (concentration 36%), phosphoric acid (concentration 85%), diammonium phosphate, ferric chloride, manganese chloride, zinc nitrate, nickel nitrate, lanthanum chloride, lanthanum oxide, ammonia water (concentration 25% to 28%), urea, sodium carbonate, sodium hydroxide, potassium hydroxide, and tetramethylammonium hydroxide: all are chemical reagents.
[0040] 4. Main catalyst: self-made, containing 33% (by weight) of Y-type molecular sieve, and the rest is binder, carrier material, rare earth. Activity of 72% after 17 hours.
[0041] Example 1 provides an MFI structured molecular sieve having the effect of the present invention. In order to better illustrate the effect of the molecular sieve of the present invention after alkali and acid modification, in Example 1, the modified molecular sieve is filtered and washed with water, and then analyzed and tested.
[0042] Example 1
[0043] 50g ZSM-5 molecular sieve A (dry basis) was added to 125mL deionized water. Under stirring, 6g sodium hydroxide and 0.5g sodium carbonate were added. The mixture was stirred at 15°C for 1h. The pH value of the molecular sieve slurry was adjusted to 1.0 with hydrochloric acid. The mixture was stirred at 40°C for 50min, then filtered, washed and dried. The molecular sieve Z-1 treated by the method of the present invention was obtained. The median particle size of the molecular sieve Z-1 was 5.6μm and the specific surface area was 368m 2 / g, mesopore volume 0.192mL / g.
[0044] The raw material ZSM-5 molecular sieve A (median particle size 7.8μm, specific surface area 340m 2 / g, mesopore volume 0.08mL / g), the median particle size of Z-1 molecular sieve becomes smaller, and the specific surface area and mesopore volume increase, indicating that the alkali treatment and acid treatment of the method of the present invention are helpful to remove silicon and aluminum in the molecular sieve, and reduce the particle adhesion between the molecular sieves, so as to achieve the purpose of dispersing the molecular sieve. After alkali and acid treatment, the specific surface area of molecular sieve Z-1 increases, and the mesopore volume increases, indicating that alkali and acid treatment are beneficial to dredge the pore structure of the molecular sieve, generate mesopores, and increase the contactable surface of the molecular sieve.
[0045] Example 2
[0046] 1140g (dry basis) ZSM-5 molecular sieve A was added to 2040mL deionized water, mixed and slurried, 136g sodium hydroxide was added, and the mixture was stirred at 25°C for 45min. The pH value of the molecular sieve slurry was adjusted to 2.5 with hydrochloric acid, 11.4g citric acid and 46g ferric chloride were added, the pH value of the slurry was 0.98, and the mixture was stirred for 45min. Then 100g phosphoric acid was added, and the stirring was continued for 15min. 2140mL deionized water, 235g aluminum chloride, 1006g (dry basis) kaolin, and 300g (dry basis) pseudo-boehmite were added, the pH value of the slurry was adjusted to 0.66, the mixture was heated to 50°C, stirred for 1 hour, and then cooled to 25°C. Under stirring, 521g phosphoric acid was added, and the mixture was stirred for 30min. The solid content of the colloid obtained was 37% (by weight). After homogenization, the mixture was spray-dried, calcined, and washed with water to obtain the additive ZJ-1 of the present invention.
[0047] Comparative Example 1
[0048] 1140 g (dry basis) of ZSM-5 molecular sieve A was added into 2040 mL of deionized water, mixed and slurried to form molecular sieve slurry DJ-1.
[0049] 2142mL deionized water, 235g aluminum chloride, 1020g (dry basis) kaolin, and 300g (dry basis) pseudo-boehmite were mixed and slurried, and the pH value of the slurry was adjusted to 0.9 with hydrochloric acid. The temperature was raised to 50°C, stirred for 1 hour, and then cooled to 25°C. Under stirring, molecular sieve slurry DJ-1 was added, and 621g phosphoric acid was added. Stirring was continued for 30 minutes. The obtained colloid had a solid content of 37% (weight). After homogenization, it was spray-dried and calcined to obtain the comparison additive DZJ-1.
[0050] Comparative Example 2
[0051] The comparative auxiliary agent DZJ-2 was prepared according to the method of Example 1 of patent CN 1796496A.
[0052] Preparation of phosphate aluminum sol: 1050g of pseudo-boehmite was mixed with 3350mL of deionized water and slurried for 30min, 4900g of phosphoric acid was added to the slurry under stirring, the temperature was raised to 70°C, and then reacted at this temperature for 45min to prepare a colorless and transparent phosphate aluminum sol.
[0053] Take 1900g (dry basis) of phosphorus-iron modified ZSM-5 molecular sieve, 1250g (dry basis) of kaolin and 650g of pseudo-boehmite, add 6200mL of deionized water and 2790g of aluminum sol, and beat for 120min. Then add 1L of FeCl 3` 6H2O (containing 100g Fe2O3). The mixture was slurried for 45 minutes, and then 1220g of phosphorus aluminum sol was added to the mixed slurry. After stirring evenly, the obtained slurry was spray-dried, formed, and calcined to obtain the comparative additive DZJ-2.
[0054] Comparative Example 3
[0055] In this comparative example, 136 g of sodium hydroxide was added, and after stirring at 25° C. for 45 min, the pH value of the molecular sieve slurry was adjusted to 7.0 with hydrochloric acid, without adding 11.4 g of citric acid. After adding ferric chloride, the pH value of the slurry was adjusted to 3.5 with ammonia water, and after adding pseudo-boehmite, the pH value of the slurry was adjusted to 3.5. The other steps were the same as in Example 2 to obtain a comparative auxiliary agent DZJ-3.
[0056] Example 3
[0057] 1050g (dry basis) of ZSM-5 molecular sieve A was added to 1900mL of deionized water, mixed and slurried, 42g of sodium hydroxide, 42g of sodium carbonate, and 15g of potassium hydroxide were added, stirred at 60°C for 1.5h, and the pH value of the molecular sieve slurry was adjusted to 4.5 with hydrochloric acid. Then 1600mL of deionized water was added, 50g of zinc nitrate, 21g of lanthanum oxide, 1015g (dry basis) of kaolin, and 360g (dry basis) of pseudo-boehmite were added, mixed and slurried, and the pH value of the slurry was adjusted to 1.8 with 18% hydrochloric acid, heated to 50°C, stirred for 1 hour, and then cooled to 25°C. Under stirring, 745g of phosphoric acid was added, and stirring was continued for 30min. The solid content of the obtained colloid was 40% (weight), and after homogenization, it was spray-dried, calcined, and washed with water to obtain the additive ZJ-2 of the present invention.
[0058] Comparative Example 4
[0059] (1) Aluminum phosphate sol binder was prepared according to the method of Example 1 of patent CN 102049284B.
[0060] 3 kg of pseudo-boehmite (dry basis) was slurried with 5.4 kg of deionized water for 30 minutes. 10.3 kg of 85% concentrated phosphoric acid was added to the slurry under stirring, followed by 5.28 kg of 68% concentrated nitric acid. The reaction was continued with stirring for 45 minutes to obtain a phosphate aluminum sol.
[0061] (2) The comparative auxiliary agent DZJ-4 was prepared according to the method of Example 2 of patent CN 102049284B.
[0062] 1.18 kg of water was added to 1.05 kg (dry basis) of ZSM-5 molecular sieve A and homogenized to prepare a ZSM-5 molecular sieve slurry.
[0063] Under stirring, 1.5 g (dry basis) of kaolin and 2.9 kg of water were mixed and slurried for 30 min, 1.5 kg of the binder prepared according to the method in step (1) was added to the kaolin slurry, and the stirring was continued for 1 h, and then the ZSM-5 molecular sieve slurry was added and stirred for 2 h. After the slurry was homogenized, it was sprayed to obtain a comparative auxiliary agent DZJ-4 containing 35 wt% of ZSM-5 molecular sieve.
[0064] Example 4
[0065] 1350g (dry basis) ZSM-5 molecular sieve B is added to 1800mL deionized water, and 500g ammonia water (concentration 25% to 28%), 70g urea, and 80g tetramethylammonium hydroxide are added under stirring, and stirred at 45°C for 1h. The pH value of the slurry is adjusted to 3.0 with nitric acid, and then 8.7g manganese chloride, 50g nickel nitrate, 30g lanthanum chloride, 931g (dry basis) diatomaceous earth, and 210g (dry basis) pseudo-boehmite are added, mixed and slurried, 10g formic acid and 20g oxalic acid are added, and the pH value of the slurry is adjusted to 0.8 with 18% hydrochloric acid, the temperature is raised to 45°C, stirred for 1h, and then cooled to 30°C. Under stirring, 566g aluminum sol, 447g phosphoric acid, and 57g diammonium hydrogen phosphate are added, and stirring is continued for 50min. The solid content of the obtained colloid is 45% (weight). After homogenization, it is spray-dried, formed, and roasted to obtain the additive ZJ-3 of the present invention.
[0066] Comparative Example 5
[0067] 1350g (dry basis) ZSM-5 molecular sieve B, 1320g (dry basis) diatomaceous earth, and 210g (dry basis) pseudo-boehmite were added to 2600mL deionized water, mixed and slurried, and the pH value of the slurry was adjusted to 0.8 with 18% hydrochloric acid. The temperature was raised to 40°C, stirred for 1h, and then cooled to 30°C. While stirring, 566g aluminum sol was added, and stirring was continued for 50min. The obtained colloid had a solid content of 45% (weight). After homogenization, it was spray-dried, formed, and calcined to obtain the comparison additive DZJ-5.
[0068] Comparative Example 6
[0069] (1) Molecular sieve A1 was prepared according to the method of Example 1 of patent CN 107971029 A.
[0070] Add 100g (dry basis) of NaZSM-5 molecular sieve to 1000g of 2.0% NaOH solution, heat to 65°C, react for 30min, quickly cool to room temperature, filter, and wash until the filtrate is neutral. Then, add 800g of water to the filter cake for slurrying, add 40g of NH4Cl, heat to 75°C, exchange for 1h, until the Na2O content is less than 0.2% by weight, filter, wash, and obtain a molecular sieve filter cake; take 50g (dry basis) of the above molecular sieve and add water to prepare a molecular sieve slurry with a solid content of 10% by weight, add 27g of oxalic acid during stirring; heat to 65°C and stir at a constant temperature for 1h, filter and wash until the filtrate is neutral; add water to the filter cake to obtain a molecular sieve slurry with a solid content of 40% by weight, add 6.1gH3PO4 (concentration 85% by weight), evenly mix, impregnate, dry, and calcine at 550°C for 2 hours. Obtain molecular sieve A1.
[0071] (2) A phosphorus-aluminum inorganic binder was prepared according to the method of Example 4 of patent CN 107971029 A.
[0072] Pseudo-boehmite (containing 1.19 kg of Al2O3), kaolin (0.50 kg on dry basis) and 3.27 kg of decationized water were slurried for 30 minutes, and 5.37 kg of concentrated phosphoric acid (mass concentration 85%) was added to the slurry under stirring at a rate of 0.04 kg phosphoric acid / min / kg alumina source. The temperature was raised to 70°C and then reacted at this temperature for 45 minutes to obtain a phosphorus-aluminum inorganic binder.
[0073] (3) The comparative auxiliary agent DZJ-6 was prepared according to the method of Example 11 of patent CN 107971029 A.
[0074] Take molecular sieve A1, kaolin and pseudo-boehmite, add decationized water and aluminum sol to slurry for 120 minutes to obtain a slurry with a solid content of 30% by weight, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to slurry for 45 minutes, then add the phosphorus aluminum inorganic binder prepared in step (2), stir for 30 minutes, and then spray dry the obtained slurry to obtain microspheres. The microspheres are roasted at 500°C for 1 hour. Take the obtained microsphere product, add ZnCl2 aqueous solution (concentration 30% by weight), heat to 60°C with stirring, react at this temperature for 20 minutes, vacuum filter and dry the slurry, and then roast at 500°C for 2 hours to obtain the comparative auxiliary agent DZJ-6.
[0075] The additives ZJ-1 to ZJ-3 prepared by Examples 2 to 4 and the comparative additives DZJ-1 to DZJ-6 prepared by Comparative Examples 1 to 6 were tested for their pore volume and wear index, respectively, and the test results are listed in Table 1. From the data in Table 1, it can be seen that the preparation process of the catalytic cracking additive prepared by the method of the present invention is simple, and the obtained additive has good strength and high pore volume. Although the strength of the additives obtained by Comparative Examples 1, 2, and 4 can meet the use requirements, the pore volume is small; the additives obtained by Comparative Examples 3, 5, and 6 have a large pore volume, but poor strength.
[0076] Table 1 Physicochemical properties of additives
[0077]
[0078]
[0079] In order to investigate the cracking reaction performance of the additive, the main catalyst, additives ZJ-1 to ZJ-3 and comparative additives DZJ-1 to DZJ-6 were aged at 800°C and 100% steam for 17 hours, and then the additives were mixed with the main catalyst at a ratio of 5% (i.e., main catalyst: additive (weight ratio) = 95:5) for evaluation. The evaluation results are listed in Table 2. In Table 2, total liquid yield = liquefied gas + gasoline + diesel.
[0080] Table 2 Results of catalytic cracking reaction selectivity evaluation
[0081]
[0082]
[0083] The data results in Table 2 show that: compared with the main catalyst, the gasoline octane number and propylene selectivity of the catalyst mixed with the catalytic cracking aids ZJ-1 to ZJ-3 provided by the present invention are significantly improved.
[0084] Compared with the catalyst mixed with the catalytic cracking aid ZJ-1 provided by the present invention, the catalyst mixed with the comparative catalytic cracking aid DZJ-1 provided in Comparative Example 1 has a total liquid yield 0.72 percentage points lower and a coke yield 0.60 percentage points higher; the gasoline octane number RON is 0.4 units lower, the propylene yield is reduced by 1.24 percentage points, and the propylene selectivity is poor (propylene / liquefied gas is low), indicating that the catalytic cracking aid prepared by the method of the present invention can significantly improve the selectivity of the catalytic cracking reaction, and increase the gasoline octane number and propylene selectivity.
[0085] Compared with the catalyst mixed with the catalytic cracking aid ZJ-1 provided by the present invention, the catalyst mixed with the comparative catalytic cracking aid DZJ-2 provided by Comparative Example 2 has a total liquid yield 0.66 percentage points lower and a coke yield 0.57 percentage points higher; the gasoline octane number RON is 0.1 unit lower, the liquefied gas yield is 1.98 percentage points higher, and the propylene yield is 0.11 percentage points lower, indicating that the catalytic cracking aid prepared by the method of the present invention has good catalytic cracking selectivity, and at the same time, the propylene yield and propylene selectivity are improved without significantly increasing the liquefied gas.
[0086] Compared with the catalyst mixed with the catalytic cracking aid ZJ-1 provided by the present invention, the catalyst mixed with the comparative catalytic cracking aid DZJ-3 provided in Comparative Example 3 has a total liquid yield 0.17 percentage points lower, a propylene yield 0.65 percentage points lower, and a gasoline octane number RON 0.3 units lower, indicating that the pH value will affect the propylene yield and the gasoline octane number. The propylene yield and the gasoline octane number of the present invention are higher when the pH value is 0.1 to 2.0.
[0087] Compared with the catalyst mixed with the catalytic cracking aid ZJ-2 provided by the present invention, the catalyst mixed with the comparative catalytic cracking aid DZJ-4 provided in Comparative Example 4 has a total liquid yield that is 0.44 percentage points lower and a coke yield that is 0.28 percentage points higher; the gasoline octane number RON is 0.2 units lower, and the propylene yield is 0.43 percentage points lower when the liquefied gas yield is equivalent, indicating that the catalytic cracking aid prepared by the method of the present invention has good catalytic cracking selectivity and significantly improves the gasoline octane number and propylene yield.
[0088] Compared with the catalyst mixed with the catalytic cracking aid ZJ-3 provided by the present invention, the catalyst mixed with the comparative catalytic cracking aid DZJ-5 provided in Comparative Example 5 has a total liquid yield 0.85 percentage points lower and a coke yield 0.54 percentage points higher; the gasoline octane number RON is 0.5 units lower, and the propylene yield is 1.33 percentage points lower when the liquefied gas yield is equivalent, indicating that the catalytic cracking aid prepared by the method of the present invention has better reaction selectivity and significantly improves the gasoline octane number, propylene yield and propylene selectivity.
[0089] Compared with the catalyst mixed with the catalytic cracking aid ZJ-3 provided by the present invention, the catalyst mixed with the comparative catalytic cracking aid DZJ-6 provided in Comparative Example 6 has a propylene yield 0.45 percentage points lower and a gasoline octane number RON 0.2 units lower, indicating that compared with the prior art, the catalytic cracking aid prepared by the method of the present invention has a simple preparation process, does not require separate alkali, acid extraction and roasting process treatment to obtain the raw material molecular sieve, the aid has better anti-wear performance, and the propylene yield and gasoline octane number are improved.
Claims
1. A catalytic cracking aid for improving the octane number of gasoline, characterized in that: The catalytic cracking aid comprises, based on 100% by mass, 10-55% of an MFI molecular sieve having a silicon oxide / aluminum oxide molar ratio of 100-450, 10-55% of clay, 3-20% of pseudo-boehmite, 5-20% of phosphorus, 0-10% of a binder, and 0.2-6% of a modified metal compound, calculated as oxide, of which the left end point 0 is not taken; the modified metal compound is selected from at least one of transition metal compounds; (I) The method for preparing the catalytic cracking aid comprises the following steps: The alkali-treated MFI structure molecular sieve, water and acid are uniformly mixed to make the pH value of the slurry in the range of 2.0 to 6.5, and then the modified metal compound and clay are added to slurry for 15 minutes to 60 minutes to form a mixed slurry A, and pseudo-boehmite is added to form a slurry B, and the pH value of the slurry B is adjusted to be in the range of 0.1 to 2.0 with acid, and then aged at 40 to 60 degrees Celsius for 30 minutes to 60 minutes, cooled to below 35 degrees Celsius, and a binder and a phosphorus compound are added, homogenized, spray-dried, roasted, and washed with water to obtain a catalytic cracking aid for improving the octane number of gasoline; or, (II) The method for preparing the catalytic cracking aid comprises the following steps: The alkali-treated MFI structure molecular sieve, water and acid are uniformly mixed to make the pH value of the slurry in the range of 2.0-6.5, and then the modified metal compound, pseudo-boehmite, clay and acid are added and mixed to form slurry C, and the pH value of the slurry C is in the range of 0.1-2.0, and then aged at 40-60° C. for 30-60 minutes, cooled to below 35° C., added with a binder and a phosphorus compound, spray dried, roasted, and washed with water to obtain a catalytic cracking aid for improving the octane number of gasoline; The alkaline treatment in (I) and (II) comprises the following steps: mixing the MFI structure molecular sieve, water and alkaline substance, and stirring at 10-80° C. for 0.5 h to 2 h; based on the dry weight of the molecular sieve, the mass ratio of the MFI structure molecular sieve: alkaline substance: water is 100: (2-50): (100-1500).
2. The catalytic cracking aid for improving the octane number of gasoline according to claim 1, characterized in that: Calculated based on 100% of the mass of the catalytic cracking aid, it contains 20-45% of MFI structured molecular sieves on a dry basis, 15-40% of clay on a dry basis, 5-15% of pseudo-boehmite on a dry basis, 10-18% of phosphorus on an oxide basis, 0-5% of a binder on an oxide basis and 0.3-4% of a modified metal compound on an oxide basis.
3. The catalytic cracking aid for improving the octane number of gasoline according to claim 1, characterized in that: The clay is selected from at least one of kaolin, metakaolin, sepiolite, rectorite, montmorillonite and diatomaceous earth; the binder is selected from at least one of alumina sol and aluminum chloride; the phosphorus is selected from at least one of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate and ammonium phosphate.
4. The catalytic cracking aid for improving the octane number of gasoline according to claim 1, characterized in that: The transition metal compound is selected from at least one of compounds of Fe, Ni, Cu, Mn or Zn.
5. The catalytic cracking aid for improving the octane number of gasoline according to claim 1, characterized in that: The transition metal compound is selected from at least one compound of Group IIIB metals in the periodic table; the Group IIIB metal in the periodic table is selected from at least one of Y and lanthanide rare earths.
6. The catalytic cracking aid for improving the octane number of gasoline according to claim 1, characterized in that: The transition metal compound is at least one selected from the group consisting of halides, nitrates and sulfates of transition metal elements that are soluble in water, and oxides, hydroxides and carbonates of transition metal elements that are insoluble in water.
7. The catalytic cracking aid for improving the octane number of gasoline according to claim 5, characterized in that: The compound of the metal of Group IIIB in the periodic table is at least one selected from the group consisting of halides, nitrates and sulfates of Group IIIB elements that are soluble in water, and oxides, hydroxides and carbonates of Group IIIB elements that are insoluble in water.
8. The catalytic cracking aid for improving the octane number of gasoline according to claim 1, characterized in that: The alkali treatment comprises the following steps: mixing the MFI structure molecular sieve, water and alkaline substance, and stirring at 15-40° C. for 0.5 h to 1 h; based on the dry weight of the molecular sieve, the mass ratio of the MFI structure molecular sieve: alkaline substance: water is 100: (4-20): (120-1000).
9. The catalytic cracking aid for improving the gasoline octane number according to claim 1 or 8, characterized in that: The alkaline substance is selected from at least one of an organic base and an inorganic base compound; the inorganic base compound is selected from at least one of ammonia water, sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium carbonate, potassium bicarbonate, potassium hydroxide, and sodium silicate; the organic base is selected from at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrapropylammonium hydroxide.
10. The catalytic cracking aid for improving the octane number of gasoline according to claim 1, characterized in that: The acid is selected from at least one of hydrochloric acid, nitric acid, phosphoric acid, oxalic acid, citric acid and formic acid.
Citation Information
Patent Citations
Catalytic cracking propylene additive and preparation method thereof
CN102049284B
Method for preparing auxiliary increasing gasoline octane number through catalytic cracking
CN106179470A
Catalytic cracking aid for increasing propylene yield, and preparation method thereof
CN107971029A
MFI structure molecular sieve containing phosphorus and transition metal
CN1465527A
Catalytic cracking aid for increasing octane number barrel of gasoline, and preparation method thereof
CN107970983A
Cited By
Assistant for increasing gasoline octane number and reducing oil slurry without increasing liquefied gas, preparation method and application
CN120624054A